Impact of Market Learning on Management Innovation: Mediating role of Knowledge Integration - Fatima, Saman; Luqman, Roshan (SEISENSE Journal of Management, 2020)
Purpose- The article aims to study and explore the effect of market learning on management innovation along with exploring the role of knowledge integration as a mediator in the hospitality industry of Pakistan. Design/Methodology- The data comprised 215 respondents from the hospitality industry, and it was gathered through a questionnaire containing 22 items, including four demographical items. The gathered data was utilized to validate our model empirically through statistical tests. Findings- Research findings reveal that management innovation is driven by market learning, and significant relationships exist between market learning, knowledge integration, and management innovation. The mediating role of knowledge integration also exists significantly between management innovation and market learning. Novelty – Knowledge integration about management innovation and market learning is a novel contribution, and findings suggest that its effect on this model is significant. Practical Implications- Successful organizations include knowledge integration and management innovation as a critical part of their culture as these variables boost the firm’s productivity and employee participation, and both are found to be driven by market learning. The managers can make an effort to enhance market learning and improve the firm’s overall performance.